Biophysical characterization and solution structure of the cannulae-forming protein CanA from the hyperthermophilic archaeon Pyrodictium abyssi - Claudia E. Munte; Raphael Kreitner; Reinhard Rachel; Karl O. Stetter; Werner Kremer; Hans Robert Kalbitzer (Scientific Reports)
Abstract CanA from Pyrodictium abyssi, the main constituent of the extracellular protein network of this archaeon, forms a hollow-fiber network in the presence of divalent ions. The polymerization of CanA induced by divalent ions is characterized by (at least) two processes with rate constants of 0.19 and 0.03 ms-1 at 298 K with a critical monomer concentration of 2.48 µM. A non-polymerizing mutant, K1-CanA, was created, and the NMR solution structure could be determined by multidimensional NMR spectroscopy. It mainly consists of β-pleated sheets and 2 small α-helices, arranged as β1β2β3β4α1β5β6α2β7β8β9β10β11β12β13. Of the 13 β-strands, 8 form a non-canonical jellyroll class I fold. Several interaction sites for divalent ions could be identified by [1H, 15N]-SOFAST-HMQC spectroscopy in two main surface areas called BA1 and BA2, located at both ends of the jellyroll. The binding of divalent ions to the monomer induces significant local structural changes in these areas. In general, the affinities for Mg2+-ions to the sites in BA1 are smaller than those for Ca2+-ions. In contrast, in binding area BA2, Mg2+- and Ca2+-affinities are similar. The data suggest a conformational selection mechanism induced by ion binding as a first step in the polymerization process of CanA.